PEMENUHAN PELAYANAN KESEHATAN BAGI NARAPIDANA PEREMPUAN DI LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS III MATARAM - Niken Meileni; Padmono Wibowo (CV. Adiba Aisha Amira, 2024)
Law Number 22 of 2022 concerning Corrections regulates the right to health services and consumption in correctional institutions, including in Article 7. This provision provides legal certainty regarding the obligation to provide the best possible services so that correctional goals can be achieved. This research aims to assess the fulfillment of health services for female prisoners and identify the obstacles faced at the Mataram Class III Women's Correctional Institution. This research method involves field studies to observe direct implementation as well as literature studies which include analysis of laws and regulations, documents and related literature. The research results show that overall, the provision of health services for female prisoners is still inadequate and not in accordance with established standards. The main obstacles are the lack of health workers, including general practitioners, and limited health equipment. However, correctional institutions have attempted to provide adequate health services by conducting health checks on sick inmates and holding other health activities.